Management of Waste Treatment as an Alternative Energy Source and its Fiscal Support - Samosir, Agunan P. (Information Management and Business Review, 2019)
In recent years, the management of waste treatment in Indonesia has become a critical issue among the stakeholders both in the government and the private sector. One way to significantly reduce waste in each region is to use incinerator technology. This technology has developed in Japan, South Korea and Europe. The burning of waste can produce electricity or the so-called waste to energy. However, to build a power plant that utilizes waste requires policy support from the Central and Regional Governments. This study seeks to identify the types of support that Central and Regional Governments can provide to develop waste to energy.